Bayesian Analyses of Ridge Regression Prooblems - Gorgees, H. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A Bayesian formulation of the ridge regression problem is considerd, which derives from a direct specification of prior informations about parameters of general linear regression model when data suffer from a high degree of multicollinearity.A new approach for deriving the conventional estimator for the ridge parameter proposed by Hoerl and Kennard (1970) as well as  Bayesian estimator  are presented. A numerical example is studied in order to   compare the performance of these estimators.